Characteristics of submucosal leiomyomas that could cause severe hemorrhage with relugolix: an observational study - Yoshimitsu Wada; Yuji Takei; Takumi Minezumi; Hiroto Hirashima; Hiroyuki Fujiwara (BMC, 2023)
Abstract Background Relugolix, an oral gonadotrophin-releasing hormone receptor antagonist, was launched in Japan in 2019. Although there have been several studies on relugolix for leiomyomas, few have focused on submucosal leiomyomas. Submucosal leiomyomas cause bleeding more frequently than leiomyomas in other locations. There is only one case report described a patient treated for a submucosal leiomyoma with relugolix who developed severe hemorrhage. However, it remains unclear which characteristics of submucosal leiomyomas can lead to severe hemorrhage. Thus, the aim of this study was to investigate the characteristics of submucosal leiomyomas that would cause severe hemorrhage when treated with relugolix. Methods We retrospectively reviewed records of patients who underwent treatment for submucosal leiomyoma with relugolix (40 mg once daily for up to 6 months) in our institute between December 2019 and September 2021. We evaluated the clinical course and characteristics of submucosal leiomyoma in patients who developed severe hemorrhage. Results A total of 17 patients were treated for submucosal leiomyoma with relugolix. Two patients developed severe hemorrhage and required emergent surgery and blood transfusions. Only those two of the 17 patients had a submucosal leiomyoma of the International Federation of Gynecology and Obstetrics (FIGO) type 0, which has a stalk. In the remaining 15 patients who had FIGO type 1 or 2 leiomyoma, hemorrhage did not occur. Conclusions Our study suggests that the use of relugolix for FIGO type 0 leiomyomas may be associated with a risk of hemorrhage. However, relugolix may be a safe and effective treatment option for patients with FIGO type 1 or 2 leiomyomas.